Metadata for digital collections : - Miller, Steven J. (Neal-Schuman Publishers, 2011)
Introduction to metadata for digital collections -- Introduction to resource description and Dublin Core -- Resource identification and responsibility elements -- Resource content and relationship elements -- Controlled vocabularies for improved resource discovery -- XML-encoded metadata -- MODS : the Metadata Object Description Schema -- VRA Core : the Visual Resources Association Core Categories -- Metadata interoperability, shareability, and quality -- Designing and documenting a metadata scheme -- Metadata, linked data, and the Semantic Web.